2017
DOI: 10.1016/j.pharep.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curcumin on acute spinal cord injury in mice via inhibition of inflammation and TAK1 pathway

Abstract: Curcumin restores mice hind-limb function that has been reduced by SCI. This occurs by inhibition of TAK1/MKK6/p38MAPK via the TAK1 and NFκB pathways and inflammation. These results suggest the therapeutic potential for curcumin in the treatment of SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Curcumin attenuated hyperglycemia-mediated TAK1 protein expression in cerebrum of streptozotocin-induced diabetic rat [29]. Moreover, curcumin decreased the phosphorylation levels of TAK1 protein and p38 MAPK in mice with acute spinal cord injury [30]. The roles of TAK1 signal pathway in EMT and peritoneal fibrosis of PMCs are in accordance with a previous report [17].…”
Section: Discussionsupporting
confidence: 86%
“…Curcumin attenuated hyperglycemia-mediated TAK1 protein expression in cerebrum of streptozotocin-induced diabetic rat [29]. Moreover, curcumin decreased the phosphorylation levels of TAK1 protein and p38 MAPK in mice with acute spinal cord injury [30]. The roles of TAK1 signal pathway in EMT and peritoneal fibrosis of PMCs are in accordance with a previous report [17].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, NF-κB activity at least in glial cells contributes to the pathogenesis of SCI. Subsequently, it has been demonstrated that curcumin ameliorates secondary damage (e.g., production of IL-6, TNF-α, IL-1β, and nitric oxide) presumably through inhibiting both the TAK1/MKK6/p38 pathway and the NF-κB pathway, which may contribute to the improvement of locomotor recovery after SCI [ 76 ].…”
Section: Involvement Of P38 In the Pathogenesis Of Scimentioning
confidence: 99%
“…Additionally, curcumin reduced reactive gliosis in the rat brain stem after ethidium bromide injection yielding smaller GFAP+ glial scar regions. [26][27][28][29]61,62 However, like a multitude of other drugs, curcumin is quite instable and poorly bioavailable so that the systemic application of the native drug will hardly achieve therapeutically relevant local concentrations. 63 In first attempts to apply curcumin locally to the brain, poly (vinyl alcohol) (PVA) based implants were loaded with curcumin and implanted into the rodent brain.…”
Section: Discussionmentioning
confidence: 99%